Understanding e-government failure in the developing country context: a process-oriented study. Issue 1 (2nd January 2017) - Gunawong, Panom; Gao, Ping
ABSTRACT: This research aims to investigate the underlying process-based causes of e-government failure. Through the lens of actor-network theory, this paper presents a process-oriented study of the failure of Thailand's Smart ID Card project. Adding to the extant knowledge on e-government failures that attributes this phenomenon to internal and external factors, this paper argues that the reason the project failed was a cumulative process of failure to create and maintain the actor-network. Policy implications for developing countries to efficiently manage their e-government initiatives are given, such as adopting an open principle in setting e-government project objectives and initiating the actor-network; implementing the e-government target in stages based on prepared environment; allowing an e-government system to evolve according to the degree of readiness in the information and communications technology (ICT) system design, implementation and local adoption; and including large, nationwide projects as part of a national informatization strategy.